Idiopatické střevní záněty jako protrombotický stav - Kamenář, David; Špičák, Julius (Vnitrni lekarstvi, 2016)
UNLABELLED: Prothrombotic states related to idiopathic bowel disease (IBD) are typically caused by abnormalities of hemostasis associated with inflammatory processes. The risk of thromboembolic complications in patients with IBD is approximately three times as high as in the general population. A critical role is played by the acquired risk factors including medication, while the proportion of inherited thrombophilia in patients with IBD is the same as in the general population. Many abnormalities can be identified through laboratory testing at the level of coagulation factors, fibrinolysis, thrombocytes and endothelium. Although there are no systematic guidelines for the prevention of thromboembolism in patients with IBD available, valid reasons for prophylactic administration of low-molecular-weight heparin are immobilization, hospitalization for IBD activity and surgery. The treatment of thromboembolism which complicates the course of IBD does not differ from its treatment among the general population, and concern over bleeding into gastrointestinal tract during anticoagulation should not outweigh the risk of possible fatal consequences of untreated thrombosis. KEY WORDS: idiopathic bowel inflammation - prothrombotic state - risk factors - thromboembolism - hereditary thrombophilia.
Keywords: idiopatické střevní záněty; trombocyty; hemostáza; Fibrinolysis; Thromboembolism; Endothelium, Vascular; koagulační faktory; fibrinolýza; antikoagulancia; tromboembolie; Blood Coagulation Factors; Humans; trombofilie; Anticoagulants; Hemostasis; cévní endotel; rizikové faktory; Heparin, Low-Molecular-Weight; Inflammatory Bowel Diseases; Blood Platelets; Thrombophilia; Risk Factors; heparin nízkomolekulární; lidé